2011
DOI: 10.1007/s11033-011-0760-z
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic membrane derived-mesenchymal stem cells induce C6 glioma apoptosis in vivo through the Bcl-2/caspase pathways

Abstract: High-grade gliomas are difficult to treat. We examined the therapeutic effect of intratumoral administration of human amniotic membrane derived-mesenchymal stem cells (hAMCs) on the growth of gliomas. Tumor volume of the control group was 1632±316 mm3 on day 30, and the group treated with a single intratumoral dose of hAMCs had a tumor volume of 1128±269 mm3 (P<0.05). Thus, administration of hAMCs significantly reduced tumor size. In rat glioma tissues treated with single and multiple dosages of hAMCs, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 27 publications
2
31
1
Order By: Relevance
“…Jiao et al reported decreased expression of Bcl-2 and high levels of apoptoticmarkers Bax, caspase-3 and caspase-8 in glioma cells after treatment with the Amniotic Stem Cells [10]. The same significant increase in caspase-3 and caspase-8 was reported in another study on HeLa and MDA-MB-231 cancer cell lines treated with Amniotic Epithelial Stem Cells [5].…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Jiao et al reported decreased expression of Bcl-2 and high levels of apoptoticmarkers Bax, caspase-3 and caspase-8 in glioma cells after treatment with the Amniotic Stem Cells [10]. The same significant increase in caspase-3 and caspase-8 was reported in another study on HeLa and MDA-MB-231 cancer cell lines treated with Amniotic Epithelial Stem Cells [5].…”
supporting
confidence: 52%
“…They suggested pro-apoptotic activities as well as anti-angiogenic and immunoregulatory capacities for the AM and argued that these properties can be applicable in cancer therapy. The hypothesised anti-cancer effects of the AM was further discussed and evaluated by Niknejad et al [5,9], Jiao et al [10] and Magatti et al [11].…”
mentioning
confidence: 99%
“…However, despite the published results so far, the action mechanisms by which hAM exerts its effects on the tumor cells are not yet fully understood [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle arrest at G0/G1 phase was observed, as well as down-regulation of genes associated with cell cycle progression and upregulation of cell cycle negative regulators. Also, Jiao et al [8] has found that hAMCs administration suppressed glioma tumor growth in vivo through the increase of pro-apoptotic proteins (BAX, caspase-3 and caspase-8) and decrease of anti-apoptotic proteins (BCL2). hAMCs conditioned medium also have anti-carcinogenic properties, inhibiting prostate cancer cells proliferation and cell cycle [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, more extensive studies documented the various differentiations of hAECs into neuron, astrocytes, pancreatic cells, cardiomyocytes, myocytes, osteocytes and adipocytes. 30 Human amniotic membrane-derived MSCs (AM-hMSCs) Amniotic membrane-human MSCs are isolated from amniotic membrane 8,16,24,26 and named AM-hMSCs. AM-hMSCs can be obtained after in vitro culture of term amnion.…”
Section: Stem Cell Characteristics Of Amniotic Membrane/ Fluid-derivementioning
confidence: 99%